1970
DOI: 10.1099/00222615-3-1-111
|View full text |Cite
|
Sign up to set email alerts
|

A New Mycoplasma Species Isolated From Pneumonic Lungs Of Calves (Mycoplasma Dispar Sp. Nov.)

Abstract: PLATES VIII-X T Y P I c A L large-colony mycoplasmas are prevalent in the upper respiratory tract of normal cattle and in the lungs of calves with pneumonia (Davies, 1967; Gunther et al., 1967;Leach, 1967) and mycoplasma T-strains have also been isolated from the latter source (Gourlay, 1968).These organisms can be cultivated by the use of the appropriate conventional mycoplasma medium, but such media are not suitable for cultivation of all types of mycoplasma, and several mycoplasmas found in animals require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

1972
1972
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(35 citation statements)
references
References 4 publications
2
32
0
1
Order By: Relevance
“…This was similar to GS broth (Gourlay & Leach, 1970) units (c.c.u.). The titre was the highest dilution that produced a colour change after incubation at 370 C. Control inocula were either uninoculated broth or broth culture of T-mycoplasmas which had been incubated at 370 C. until viable organisms could no longer be demonstrated (dead organisms).…”
Section: Strains Of T-mycoplasmasupporting
confidence: 67%
See 1 more Smart Citation
“…This was similar to GS broth (Gourlay & Leach, 1970) units (c.c.u.). The titre was the highest dilution that produced a colour change after incubation at 370 C. Control inocula were either uninoculated broth or broth culture of T-mycoplasmas which had been incubated at 370 C. until viable organisms could no longer be demonstrated (dead organisms).…”
Section: Strains Of T-mycoplasmasupporting
confidence: 67%
“…Four strains of T-mycoplasmas were used: the A417 strain that had been isolated from a pneumonic calf lung (Gourlay & Thomas, 1970), the D32 strain that had also been isolated from a pneumonic calf lung (calf 24, table 1, Gourlay, Mackenzie & Cooper, 1970), the REOW strain isolated from the human urogenital tract and supplied by Dr D. Taylor-Robinson, and the M 126/68 strain also isolated from the human urogenital tract and supplied by Dr B. E. Andrews. Two different substrains of the A 417 strain were used; the first was at the 10-11 dilution from the original lung tissue while the second -'cloned' -had undergone six subcultures in broth of which three had been from the terminal dilution, as a means of purification, and was at a 10-25 dilution from the original lung.…”
Section: Strains Of T-mycoplasmamentioning
confidence: 99%
“…Mycoplasmas were grown in glucose calf-serum (GS) broth (Gourlay & Leach, 1970) containing ampicillin (Andrews, Leach, Gourlay & Howard, 1973) except when organisms were grown for injection into rabbits, in which case rabbit digest broth and rabbit serum, heated at 56°C. for 30 min.…”
Section: Mediamentioning
confidence: 99%
“…M. hominis (Purcell et al 1967) M. gallisepticum (Taylor-Robinson & Berry, 1969) and M. pulmonis (Forshaw & Fallon, 1972) have shown these species to be serologically heterogeneous and to contain various subtypes. No serological comparison of a group of M. dispar strains has been made except for that of Gourlay & Leach (1970) who found that antiserum to strain 462/2 inhibited the growth on agar of 23 out of 36 strains examined. As little information is available on the serological heterogeneity or homogeneity of the species the first part of this study deals with this aspect of M. dispar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation